2013
DOI: 10.1021/am4031054
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Magnetoelectric Response of Poly(vinylidene fluoride)/Epoxy/Vitrovac Laminates

Abstract: The effect of the bonding layer type and piezoelectric layer thickness on the magnetoelectric (ME) response of layered poly(vinylidene fluoride) (PVDF)/epoxy/Vitrovac composites is reported. Three distinct epoxy types were tested, commercially known as M-Bond, Devcon, and Stycast. The main differences among them are their different mechanical characteristics, in particular the value of the Young modulus, and the coupling with the polymer and Vitrovac (Fe39Ni39Mo4Si6B12) layers of the laminate. The laminated co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
77
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 47 publications
1
77
4
Order By: Relevance
“…Preparation of bulk 2-2 laminate composites has been mainly conducted by epoxy bonding and co-firing [5,[22][23][24][25][26]. The most common geometries in laminate composites are either bilayer structure of magnetostrictive and piezoelectric layers or a sandwich structure, whereby the piezoelectric layer is arranged between two magnetostrictive ones.…”
Section: Bulk Me Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Preparation of bulk 2-2 laminate composites has been mainly conducted by epoxy bonding and co-firing [5,[22][23][24][25][26]. The most common geometries in laminate composites are either bilayer structure of magnetostrictive and piezoelectric layers or a sandwich structure, whereby the piezoelectric layer is arranged between two magnetostrictive ones.…”
Section: Bulk Me Compositesmentioning
confidence: 99%
“…This composite structure yielded a giant ME response with an extremely low equivalent magnetic noise. Some polymer-based laminate ME composites prepared using polyvinylidene difluoride (PVDF), a piezopolymer possessing a low ε and a high g, in combination with Metglas or Vitrovac (Fe-based amorphous alloy) and Terfenol-D, have also shown large ME coupling behavior [25,26]. Figure 3.…”
Section: Bulk Me Compositesmentioning
confidence: 99%
“…Table 1 summarizes the obtained mean magnetic parameters for all the used magnetostrictive alloy compositions [11]. Polymer-based ME laminates are typically produced by epoxing magnetostrictive layers (Metglaslike or Vitrovac; M) to commercial poled β-PVDF (P), following the optimized conditions presented in previous studies [14,15]. All the laminates appearing within this work are bilayers (MP) or three-layer sandwich-like (L-T type, MPM) laminated composites.…”
Section: Materials: Magnetostrictive and Piezoelectric Constituentsmentioning
confidence: 99%
“…[14][15][16][17][18] It does not show the above shortcomings of conventional transducers and meet the wearable device demands of being flexible, lightweight, easy fabrication, large scale production and biocompatibility. 19 Actually, flexibility not only provides an additional function during application, but it also enables a more simply integration process on non-planar or even curved surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Silva et al reported a PVDF/Vitrovac 4040 transducer which were bonded with epoxies with different elastic moduli to investigate the effect of the bonding layer type. 17 However, in spite of the large ME response, the MPM structure means to add an additional layer of epoxy resin. It will reduce the flexibility of transducers, which may make it not sufficient for a broader area of application.…”
Section: Introductionmentioning
confidence: 99%